PROGRAM PELATIHAN KESEJAHTERAAN KESEHATAN MASYARAKAT DENGAN KONSEP âDUSUN SIAGA KESEHATANâ DI DUSUN PAJIMATAN â PAYAMAN UTARA, GIRIREJO, IMOGIRI, BANTUL, YOGYAKARTA - Yudantoko, Afri; Prasetyo, Anang; Cahyadi, Ingge Septia; Pitoyo, Gangsar; Amal, Ikhlasul (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
To realize available workers with high quality and high competitiveness, health development should be directed to consciousness increasing, desire and ability to live healthy for everybody so that the societyâs high health can be realized. The degree of health, education, and economy are the main pillar which have a strong connection with the imrpovement of available workersâ quality, therefore, it is expected that the available workers can be persistent, productive, and able to compete to face all challenge that may be found (Healthy Minister, 2010). For that case, we, as the young generation who are really expected in giving real contribution for realizing a brighter future for Indonesia, should participate in taking concrete actions in developing the concept of âDusun Siaga Kesehatanâas an effort to develop society life which has high conciousness in healthy life based on cooperation principle and social movement. The aims of this report composing are to know the concept of âDusun Siaga Kesehatanâas an effort of national healthy development based on societyâs healthy and to know the development of âDusun Siaga Kesehatanâas an effort of national healthy development based on societyâs healthy. The typical character of âDusun Siaga Kesehatanâ is appearance of some activities related to readiness of the village to anticipate and to handle the health in the village. The appearance of the good character in the society is because they make it as a habit in their life. âDusun Siaga Kesehatanâ gives a concept of society life which respects deeply the essence of mutual assistance and caring to create a healthy society environment. âDusun Siaga Kesehatanâ involves the whole counrtyside society in the program accomplishing to motivate the social movement in the effort of natioanl health based on societyâs health. The development of âDusun Siaga Kesehatanâ needs some methods which are integrated and continued. One of them is by using managerial principle, those are planning, acting, evaluating, and controlling. The managerial principle is expected to motivate the social movement in the effort of national health development based on societyâs health.